2009
DOI: 10.2353/ajpath.2009.080537
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Activates the PI3K/Akt/mTOR Pathway in Muscle and Ameliorates Pathology in a Mouse Model of Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy is a lethal neuromuscular disease that currently has no effective therapy. Transgenic overexpression of the ␣7 integrin in mdx/ utrn ؊/؊ mice, a model of Duchenne muscular dystrophy ameliorates the disease. We have isolated and used ␣7 ؉/؊ muscle cells expressing ␤-galactosidase, driven by the endogenous ␣7 promoter, to identify compounds that increase ␣7 integrin levels. Valproic acid (VPA) was found to enhance ␣7 integrin levels, induce muscle hypertrophy, and inhibit apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 28 publications
3
62
0
Order By: Relevance
“…Our results indicate that mTOR signaling is also activated in tissues of the CB, PFC and HC in VPA-induced ASD rats. This result is consistent with Gurpur's report on VPA-exposed muscle (Gurpur et al, 2009) and different from the finding from Nicolini's study (Nicolini et al, 2015). In Nicolini's study, the tissue of fusiform gyrus from human brain and the lateral temporal neocortices from VPA-exposed rats was used to examine the activation of mTOR signaling.…”
Section: Discussionsupporting
confidence: 84%
“…Our results indicate that mTOR signaling is also activated in tissues of the CB, PFC and HC in VPA-induced ASD rats. This result is consistent with Gurpur's report on VPA-exposed muscle (Gurpur et al, 2009) and different from the finding from Nicolini's study (Nicolini et al, 2015). In Nicolini's study, the tissue of fusiform gyrus from human brain and the lateral temporal neocortices from VPA-exposed rats was used to examine the activation of mTOR signaling.…”
Section: Discussionsupporting
confidence: 84%
“…In that study, Ribeiro et al (48) found that altered regulation of integrin trafficking in mtm-deficient flies was linked to muscle attachment and maintenance defects that are remarkably similar to those observed in XLMTM disease. This observation is especially intriguing in light of our finding that myotubularin regulates Akt signaling because disruption of integrin trafficking has previously been linked to impaired Akt signaling, pro-apoptotic signaling, and skeletal muscle atrophy (49,50). In addition, PIK3C2B has also been shown to regulate integrin trafficking and inhibit Akt phosphorylation in mammalian cells (51).…”
Section: Discussionmentioning
confidence: 96%
“…Activation of Akt signaling promotes skeletal muscle hypertrophy (21)(22)(23), functioning through multiple signaling proteins involved in both survival and apoptotic pathways in skeletal muscle (24). Akt also protects cells from apoptosis by stimulating glucose transport in the cells and the recruitment of hexokinases to mitochondria (62).…”
Section: Discussionmentioning
confidence: 99%